On (3,3)-Gaussian quadratic stochastic operators - Ganikhodjaev, Nasir; Hamzah, Nur Zatul Akmar (IOP Publishing, 2017)
In this paper, we define (n, k)-Gaussian quadratic stochastic operators and investigate the trajectory behavior of (3, 3)-Gaussian quadratic stochastic operators. It is established the necessary and sufficient conditions for regularity of these operators.